The Complex Repeats of Dictyostelium discoideum - Glöckner, Gernot; Szafranski, Karol; Winckler, Thomas; Dingermann, Theodor; Quail, Michael A.; Cox, Edward; Eichinger, Ludwig; Noegel, Angelika Anna; Rosenthal, André (Genome Research, 2001)
In the course of determining the sequence of the Dictyostelium discoideum genome we have characterized in detail the quantity and nature of interspersed repetitive elements present in this species. Several of the most abundant small complex repeats and transposons (DIRS-1; TRE3-A,B; TRE5-A; skipper; Tdd-4; H3R) have been described previously. In our analysis we have identified additional elements. Thus, we can now present a complete list of complex repetitive elements in D. discoideum. All elements add up to 10% of the genome. Some of the newly described elements belong to established classes (TRE3-C, D; TRE5-B,C; DGLT-A,P; Tdd-5). However, we have also defined two new classes of DNA transposable elements (DDT and thug) that have not been described thus far. Based on the nucleotide amount, we calculated the least copy number in each family. These vary between <10 up to >200 copies. Unique sequences adjacent to the element ends and truncation points in elements gave a measure for the fragmentation of the elements. Furthermore, we describe the diversity of single elements with regard to polymorphisms and conserved structures. All elements show insertion preference into loci in which other elements of the same family reside. The analysis of the complex repeats is a valuable data resource for the ongoing assembly of whole D. discoideum chromosomes.[The sequence data described in this paper have been submitted to the GenBank data library under accession nos. AF135841, AF298201, AF298202, AF298203, AF298204,AF298205, AF298206, AF298207, AF298208, AF298209, AF298210 and AF298624.]
10.1101/gr.162201